Establishing a new paradigm for music education in China: from a constructivist perspective - Ji, Jieying (Kansas State University, 2013)
This report presents a feasibility study of operating constructivism in Chinese music education. Major problems have been discussed in each chapter, including the historical background of music education in China, and a philosophical rethinking of current situations in China. Questions have arisen: what is constructivism? Why would it be a new changing point for Chinese music education? What needs to be done to apply constructivism in China? China has a strong background of behavior-focused education. Because of that, music education falls into a teacher directed model, and often loses its impact in public schools for students. But as the development of economy in a worldwide context and a collaboration of multi-cultural environments, music should be recognized as an important role for promoting active learning and cultural understanding. Therefore, music educators in China need to start exploring in new directions for development of music education. Constructivism, as a learning theory provides an understanding of how students learn. Based on constructivism, students would develop their own understanding of knowledge, and build their independent learning skills. Constructivism presents how students truly learn, and it could lead to a new paradigm of music education in China.
Keywords: Music education; Constructivism; China; Learning; Music Education (0522)